Hybrid Nanoparticles of Proanthocyanidins from Uncaria tomentosa Leaves: QTOF-ESI MS Characterization, Antioxidant Activity and Immune Cellular Response - Araya Sibaja, Andrea Mariela (2022)
Previous studies in Uncaria tomentosa have shown promising results concerning the characterization of polyphenols with leaves yielding more diverse proanthocyanidins and higher bioactivities values. However, the polyphenols-microbiota interaction at the colonic level and their catabolites avoid the beneficial effects that can be exerted by this medicinal plant when consumed. In this regard, a new generation of hybrid nanoparticles has demonstrated improvements in natural compounds’ activity by increasing their bioavailability. In this line, we report a detailed study of the characterization of a proanthocyanidin-enriched extract (PA-E) from U. tomentosa leaves from Costa Rica using UPLC-QTOF-ESI MS. Moreover, two types of hybrid nanoparticles, a polymeric-lipid (F-1) and a protein-lipid (F-2) loaded with PA-E were synthesized and their characterization was conducted by dynamic light scattering (DLS), attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FT-IR), high-resolution transmission electron microscopy (HR-TEM), and encapsulation efficiency (%EE). In addition, in vitro release, antioxidant activity through 2,2-diphenyl-1-picrylhidrazyl (DPPH) as well as in vivo delayed-type hypersensitivity (DTH) reaction was evaluated. Results allowed the identification of 50 different compounds. The PA-E loaded nanoparticles F-1 and F-2 achieved encapsulation efficiency of ≥92%. The formulations exhibited porosity and spherical shapes with a size average of 26.1 ± 0.8 and 11.8 ± 3.3 nm for F-1 and F-2, respectively. PA-E increased its release rate from the nanoparticles compared to the free extract in water and antioxidant activity in an aqueous solution. In vivo, the delayed-type hypersensitive test shows the higher immune stimulation of the flavan-3-ols with higher molecular weight from U. tomentosa when administered as a nanoformulation, resulting in augmented antigen-specific responses. The present work constitutes to our knowledge, the first report on these bioactivities for proanthocyanidins from Uncaria tomentosa leaves when administrated by nanosystems, hence, enhancing the cellular response in mice, confirming their role in immune modulation.